Antiviral activity of bone morphogenetic proteins and activins - Eddowes, LA; Al-Hourani, K; Ramamurthy, N; Frankish, J; Baddock, HT; Sandor, C; Ryan, JD; Fusco, DN; Arezes, J; Giannoulatou, E; Boninsegna, S; Chevaliez, S; et al. (Springer Nature, 2018)
Understanding the control of viral infections is of broad importance. Chronic hepatitis C virus (HCV) infection causes decreased expression of the iron hormone hepcidin, which is regulated by hepatic bone morphogenetic protein (BMP)/SMAD signalling. We found that HCV infection and the BMP/SMAD pathway are mutually antagonistic. HCV blunted induction of hepcidin expression by BMP6, probably via tumour necrosis factor (TNF)-mediated downregulation of the BMP co-receptor haemojuvelin. In HCV-infected patients, disruption of the BMP6/hepcidin axis and genetic variation associated with the BMP/SMAD pathway predicted the outcome of infection, suggesting that BMP/SMAD activity influences antiviral immunity. Correspondingly, BMP6 regulated a gene repertoire reminiscent of type I interferon (IFN) signalling, including upregulating interferon regulatory factors (IRFs) and downregulating an inhibitor of IFN signalling, USP18. Moreover, in BMP-stimulated cells, SMAD1 occupied loci across the genome, similar to those bound by IRF1 in IFN-stimulated cells. Functionally, BMP6 enhanced the transcriptional and antiviral response to IFN, but BMP6 and related activin proteins also potently blocked HCV replication independently of IFN. Furthermore, BMP6 and activin A suppressed growth of HBV in cell culture, and activin A inhibited Zika virus replication alone and in combination with IFN. The data establish an unappreciated important role for BMPs and activins in cellular antiviral immunity, which acts independently of, and modulates, IFN.